FINANCIAL LITERACY TRAINING TO INCREASE SELF-CAPACITY STUDENTS AT IT IZZATUNA HIGH SCHOOL - Lidia Desiana; Muhamad Rahman Bayumi; Nur Hesthria; Fernando Africano (CV. Doki Course and Training, 2023)
Islamic banking is currently growing rapidly and this can be seen from the increasingly complete Islamic bank products. The presence of Islamic bank products can certainly be an option in order to prioritize Islamic principles. Basically, Islamic banks carry out the same three functions as conventional banks, it's just that Islamic bank products have very different principles from conventional banks. Islamic bank products generally apply a profit-sharing system that is mutually beneficial for customers and banks. In this article, we will discuss further about the products and services contained in Islamic banks.